The most gender-equal Olympics? A corpus-assisted keywords analysis of Italian press coverage of male and female athletes in Paris 2024 - Frabotta, Simona; Fernández-Cruz, Javier (Universitat Politècnica de València, 2025)
The Paris 2024 Olympic Games were the most gender-equal in athlete participation. This article analyzes Italian media coverage to assess the representation of male and female athletes, focusing on narrative equality and gender biases. Using a corpus of Italian daily journal articles, we conducted a Corpus-Assisted Discourse Analysis. Results show that women’s sports received less coverage than men’s, are more likely to be represented in traditionally “feminine” sports like gymnastics, while in other sports they were underrepresented. The media emphasized gender and regulatory issues, especially concerning transgender athletes. Additionally, female athletes were often depicted through emotional lenses, while male athletes were framed through competitiveness and achievement. Despite growing participation equality, media portrayals of athletes remain influenced by traditional gendered narratives, indicating a need for further examination as sports media evolves.
PID2020-115310RB-I00 PID2022-141057OBI00
Keywords: Lenguaje no sexista; Lengua italiana - Análisis del discurso; Olympics; Corpus-assisted discourse studies; Gender studies; Italian studies; New analysis